2022
DOI: 10.3390/foods11152296
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial and Antibiofilm Activity of Oregano Essential Oil against Enterococcus faecalis and Its Application in Chicken Breast

Abstract: Oregano essential oil (OEO) possesses anti-inflammatory, antioxidant, and cancer-suppressive properties. Enterococcus faecalis is a foodborne opportunistic pathogen that can be found in nature and the food processing industry. The goal of this investigation was to explore the antimicrobial action and mechanism of OEO against E. faecalis, inactivation action of OEO on E. faecalis in mature biofilms, and its application in chicken breast. The minimum inhibitory concentration (MIC) of OEO against E. faecalis stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The high incidence of resistant Candida species and the associated negative consequences and therapeutic limitations make it crucial to develop effective, inexpensive, and nontoxic alternative treatments. In this sense, OEO has demonstrated good fungicidal and bactericidal activities against different pathogens ( 28 30 ). Recent studies also showed that the volatile part of the EO (VP-OEO) has interesting antimicrobial activity ( 31 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…The high incidence of resistant Candida species and the associated negative consequences and therapeutic limitations make it crucial to develop effective, inexpensive, and nontoxic alternative treatments. In this sense, OEO has demonstrated good fungicidal and bactericidal activities against different pathogens ( 28 30 ). Recent studies also showed that the volatile part of the EO (VP-OEO) has interesting antimicrobial activity ( 31 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…As already emphasized, there are few studies analyzing the antibacterial effect of phytobiotic products on the most common Enterococcus strains in broilers (reference strains and strains occurring in industrial breeding) [45,46]. The problem of comparing results probably stems from the fact that the mixture of phytobiotics used in the experiment has a unique composition, not found in any other preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, biofilm has become a worldwide public health. According to the literature data, it is worth noting that many Enterococcus strains can build biofilms on food contact surfaces [ 18 ]. In the current study, 73.5% isolates from raw milk and 47.2% isolates from cheeses exhibited great biofilm-forming ability.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of biofilms on work surfaces may result in the contamination of food products with both spoilage and pathogenic microorganisms [ 17 ]. Many Enterococcus strains can form biofilms on food contact surfaces, which improve bacteria’s resistance to environmental stress [ 18 ]. It is worth noting that the modernity of the equipment used in the dairy industry and, consequently, the long-lasting production cycles and the associated extensive surfaces of materials in direct contact with foods, provide favorable conditions for the unhindered formation and development of a bacterial biofilm.…”
Section: Introductionmentioning
confidence: 99%